THE STUDENT’S PRODUCTION OF SPEECH SOUND DISORDER AND ITS CAUSES - Dwi Puji Nurhayati; Fahrus Zaman Fadhly; Wulan Rahmatunisa (Indonesian Journal of Learning and Instruction, 2021)
This research investigated the production of speech sound disorder student and the cause of student’s speech sound disorder, precisely in stuttering type. Unicomb, Hewatt, Spencer, and Harrison (2017) considered stuttering as the lack of neurology condition which disturbs the speech’s flow and erratic obstacle in communication process. There was only 1 participant involved in this study namely a student in one of vocational high school in Kuningan. This study used a qualitative approach, mainly case study that gathered the data through observation and interview. Based on the result, among three types of stuttering which are prolongation, repetition and blocks, the production of the participant that mainly occurred were repetition and blocks. Thus, the cause of the participant’s stuttering was due to the lack of coordinator between the nerve and articulator and also it became worse because the anxiety. Keywords: Speech sound disorder; stuttering; production